Identification of the critical cultivation parameters for scaling up the upstream process of recombinant human Follicle Stimulating Hormone production from Chinese Hamster Ovary cells - Amer, Momen Mohsen (AUC Knowledge Fountain, 2014)
Biotechnology industry has experienced a massive development in the production of recombinant protein therapeutics over the past few decades. Stainless steel bioreactors have been considered the gold standards for the upstream processing for a long time. However, over the past decade, the single use technology has gained a big interest in the field especially with the mammalian and insect cell cultures. The single use based processes offered many advantages over the conventional ones. Disposable systems eliminated the need for cleaning in place (CIP), sterilization in place (SIP) and cleaning validation, reduced the risks of cross contamination, and they also offered less production turnaround times. In 2010, Rhein Minapharm Biogenetics, a leading company in biopharmaceutical production in the Middle East, presented the first single use technology based upstream process for recombinant human- follicle stimulating hormone (rh-FSH) production from Chinese hamster ovary (CHO) cells on the HyClone 50L single use bioreactor (SUB). The process was then scaled up to the BIOSTAT STR 200L bioreactor. However, although the BIOSTAT STR 200L bioreactor offered a higher cell density, the product concentration measured by ELISA was only two thirds, the concentration on HPLC was about 75% and the specific cell productivity was only about 50% when compared to the HyClone 50L SUB process. In the current study, the operational parameters that were observed to be different in the two processes were examined. The aim was to determine the critical cultivation parameters to be considered during the scaling of the process. Those parameters were tested at different operating values covering a wide but reasonable range. The experiments were run on the DASGIP lab scale bioreactor at a 750mL working volume. The tested parameters were the culture cell density, the carbon dioxide partial pressure (pCO2) and osmolality levels in the culture, and the effect of operating at as much as 10 folds higher power input per unit volume (P/V), the parameter which was also tested on the 200L scale. The experiments on the lab scale showed that the lower cell density and the higher pCO2 and osmolality levels, being comparable to those of the 50L process yielded results comparable to the HyClone 50L SUB process. On the other hand, operating at higher cell density and lower pCO2 and osmolality levels, being comparable to those of the 200L process, yielded results comparable to the BIOSTAT STR 200L process. No remarkable differences were observed either in the cell growth rate, the product titer or in the cell productivity when operating at P/V of ten folds difference. It was concluded that the cell density and the pCO2 and/or osmolality levels are the critical cultivation parameters in the lab scale experiments. These parameters are to be on focus and to be carefully optimized during scaling up of the process.